Pentingnya Pendidikan Seksual Anak Usia Dini - Ode Yahyu Herliany Yusuf; Muhammad Syukran; Melianti; Wa Ode Rahmadani; Hisna; Ainna Putri; Wa Ode Amira Fahrani; Satriwati (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Community service activities are activities that include efforts to improve the quality of human resources, knowledge and broaden horizons. Sex education is an effort to teach, raise awareness and provide information about sexual problems. The information provided includes knowledge about the function of the reproductive organs by instilling morals, ethics, commitment, religion so that "abuse" of the reproductive organs does not occur. Sex education is very important given from an early age. Knowledge about sex in children can prevent sexual deviations in children. Sex education for children can also prevent children from becoming victims of sexual harassment, by being equipped with knowledge about sex, they will understand which behaviors are classified as sexual harassment. Knowledge of sex can also prevent children from experimenting with things they should not be allowed to do because of their ignorance.